Experimental study on anti-freezing and thawing of preparation of wet mixed mortar with full component recycled sand in plastering engineering. Issue 1 (June 2021) - Yang, Yuhao; Jin, Shengji; Cao, Fubo
Abstract: In this study, in order to study the freeze-thaw resistance of wet-mix plaster mortar after replacing artificial sand (AS) with full-component recycled sand (FCRS) and recycled brick powder (RBP) instead of fly ash (FA), ratio of binding material to fine aggregate (RBMFA) (1:5, 1:6 and 1:7), types of fine aggregate (TFA) (AS and FCRS) and kinds of mineral admixture (KMA) (FA and RBP) were considered as research variables. RBMFA, TFA and KMA have an effect on freeze-thaw resistance performance of wet mixed mortar (WMM) could be studied with the slow freezing method. Moreover, new way of application of brick powder was explored. Take advantage of full-component recycled fine aggregate instead of traditional AS to prepare wet mix plaster mortar (WMPM) have three meanings of saving natural resources, protecting the environment and achieving superior economic benefits. Numerical studies indicated that RBMFA is one of the most main influence factors of the freezing and thawing resistance of mortar. Under 25 freeze-thaw cycles, mass loss rate (MLR) and strength loss rate (SLR) of mortar increase with the reduction of rubber sand ratio, the average MLR of RBMFA 1:7 to 1:5 increased by 2.5%, and the average SLR increased by 7.4%. Replacing AS with FCRS and replacing BP with FA can not only alleviate the shortage of natural sand and FA, but also it could realize the resource utilization of building waste.